The Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja PNS Pada BPKAD Kabupaten Karawang - Erica Julianthi Priatna; Dede Jajang Suyaman; Sonny Hersona GW (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is intended to test the effect of training on the performance of civil servants in BPKAD Karawang Regency. This research sample covered 52 civil servants in BPKAD Karawanng Regency. The results of multiple linear regression analysis found that training and motivation variables had a positive effect on employee performance. This study shows that job training has an influence on employee performance. Agency policies on improving good job training in a sustainable basis need to be done in order to maintain quality and improve employee performance. Keywords: training, motivation, performance.